Modeling of barrier in the adoption of omnichannel marketing: a case of Indian handloom industry - Naik M.K.P.; Bhardwaj P.; Mishra V. (My University, 2025)
Purpose: This study aims to explore the essence of the omnichannel in the handloom industry’s development and to identify, analyse and estimate the barriers obstructing the implementation of the omnichannel in the handloom industry of India. Design/methodology/approach: A descriptive literature review and expert opinion are used to identify the barriers obstructing the successful realisation of the omnichannel in the handloom industry of India. Moreover, interpretive structural modeling and the matrix of cross-impact multiplications applied to classification are used to analyse and estimate the impact of these barriers. Findings: This research suggests the implementation of the omnichannel is subjected to several barriers, specifically lack of government support and policies, uncertainty in business contract partners, poor reverse logistics system, etc. Originality/value: This research explores the contribution of the handloom industry to the socioeconomic development of the rural and semi-urban Indian population. It also explores the need for government support for the survival and growth of the handloom industry. It also explains how omnichannel can support this industry for its survival and its overall development. Furthermore, factors inhibiting the implementation of the omnichannel in the handloom industry are identified and evaluated based on their over impact. © 2023, Emerald Publishing Limited.